2018
DOI: 10.12659/msm.907461
|View full text |Cite
|
Sign up to set email alerts
|

ALG3 Is Activated by Heat Shock Factor 2 and Promotes Breast Cancer Growth

Abstract: BackgroundPrevious research found that ALG3 is associated with cervical cancer, but the role of ALG3 in breast cancer was still unknown.Material/MethodsThe expression of ALG3 in breast carcinoma tissues was determined by immunochemistry. The ability of cellular proliferation, migration, and invasion was determined by CCK-8 assay, wound healing migration assay, and cell invasion assays, respectively. The binding between HSF2 and promoter of ALG3 was determined by ChIP assay.ResultsThere was an increased express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…According to previous studies, ALG3 has been reported to be an underlying treatment target in non-small cell lung cancer [15], and high expression of ALG3 was positively correlated with the rapid development and poor prognosis of breast cancer patients [10]. Similar to previous studies, our results discovered that ALG3 was highly expressed in OSCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to previous studies, ALG3 has been reported to be an underlying treatment target in non-small cell lung cancer [15], and high expression of ALG3 was positively correlated with the rapid development and poor prognosis of breast cancer patients [10]. Similar to previous studies, our results discovered that ALG3 was highly expressed in OSCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 88%
“…By analyzing the TCGA database including 338 OSCC tumor and 32 normal tissues, ALG3 was picked up for further exploration. The data from TCGA presented that ALG3 was obviously enhanced in OSCC tumor tissues, which was consisted with the expression in esophageal squamous cell carcinoma and breast cancer [8,10] (Fig. 1A, p=4.735e-03).…”
Section: Alg3 Expression Was Associated With Overall Survival Of Osccmentioning
confidence: 90%
“…Recently and in line with this, ALG3 was also detected in cellular compartments apart from the ER, albeit the function of this protein in the cytosol and nucleus remains unclear (Hacker, Schultheiss, & Kurzik‐Dumke, ; Hacker, Schultheiss, Doring, & Kurzik‐Dumke, ). Furthermore, ALG3 seems to be associated with cervical cancer (Yang et al, ) and was also found to affect drug‐resistance in acute myeloid leukemia cells (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The miR-183/-96/-182 cluster then promotes the migration and survival of breast cancer cells by inhibiting the expression of the tumor suppressor RAB21 [36]. In breast cancer cells, HSF2 can regulate ALG3 enzyme expression to enhance cell proliferation and migration [37]. Moreover, knockdown of ALG3 reduces tumor growth and HSF2 expression levels, indicating feedback between HSF2 and ALG3 [37].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cells, HSF2 can regulate ALG3 enzyme expression to enhance cell proliferation and migration [37]. Moreover, knockdown of ALG3 reduces tumor growth and HSF2 expression levels, indicating feedback between HSF2 and ALG3 [37]. Moreover, miR-202 is aberrantly expressed in ESCC and negatively regulates apoptosis by directly targeting HSF2 and subsequently affecting HSP70 expression [25].…”
Section: Discussionmentioning
confidence: 99%